Developing an Addictions Nursing Competency Framework Within a Canadian Context. Issue 3 (July 2017) - Ling, Sara; Watson, Alison; Gehrs, Margaret
Abstract : Abstract: Clients with substance use disorders access care in all areas of the health care system, yet the Canadian nursing literature lacks content on the knowledge, skills, and judgment needed by nurses who work with this population. To address this literature gap, two Advanced Practice Nurses adapted the Canadian Centre on Substance Abuse's Technical Competencies for Canada's Substance Abuse Workforce to include nursing content and theory. This article describes the adaptation process and validation method used by the Advanced Practice Nurses at a large, Canadian urban teaching hospital and includes discussion about actual and potential opportunities for practical application of the adapted framework.